Motion discrimination in cortically blind patients. - Azzopardi, P; Cowey, A (2001)
Some patients with brain damage affecting the striate cortex, though clinically blind in their field defects, can still discriminate visual stimuli when forced choice procedures are used. Such patients seem particularly sensitive to moving stimuli in their scotomata, though there are conflicting reports as to whether they can discriminate the direction of motion. We tested three patients with areas of cortical blindness for their ability to detect and discriminate the direction of motion of a variety of first-order motion stimuli, namely bars, gratings, plaids and random dot kinematograms depicting translation and motion in depth, during forced choice tasks. The patients could detect the presence of movement in any kind of stimulus, and could discriminate the direction of single bars, but none could discriminate the direction of motion of the more complex stimuli (gratings, plaids and random dot kinematograms) or discriminate between 0 and 100% coherent random dot kinematograms at any speed tested (from 4 to 64 degrees /s). Similar results were obtained from one of the patients who was additionally tested with second-order versions of the translated bar and random dot kinematograms, eliminating light scatter as an explanation. Overall, the results suggest that motion processing in the scotoma is severely impaired, and that the puzzling discrepancies between previous studies can be accounted for by the type of stimulus used. The motion discrimination impairment caused by brain damage affecting the primary visual cortex is inconsistent with the proposed existence of a subcortical pathway to extrastriate cortical motion areas (such as areas MT and MST) which bypasses the striate cortex and is specialized for analysing 'fast' motion.